THE IMPACT OF INTERNATIONAL FINANCIAL INSTITUTIONS ON POST-PANDEMIC ECONOMIC RECOVERY: ANALYSIS OF CHINA AND THE UNITED STATES - Gofurova Umida Khidirnazar qizi; Gulyamova Gulshaxnoz Sabirovna (Modern American Journals, 2025)
The COVID-19 pandemic caused an unprecedented global economic crisis, prompting international financial institutions (IFIs) to play a critical role in supporting recovery efforts. This article analyzes the influence of IFIs—such as the International Monetary Fund (IMF), World Bank, and Asian Infrastructure Investment Bank—on the post-pandemic economic recovery processes in China and the United States. By comparing the financial strategies, policy interventions, and structural support provided to each country, the study highlights differences in institutional impact based on national economic models and governance structures. The article also examines how cooperation with IFIs has shaped fiscal and monetary responses, investment flows, and resilience-building efforts in both economies. The findings contribute to a deeper understanding of the evolving role of IFIs in fostering sustainable and inclusive global recovery.
Keywords: Post-pandemic recovery, international financial institutions, IMF, World Bank, China, United States, economic resilience, fiscal policy, monetary policy, global financial cooperation.